Feasibility studies for a wireless 60GHz tracking detector readout - Dittmeier, Sebastian; Schöning, André; Soltveit, Hans Kristian; Wiedner, Dirk (Nuclear instruments & methods in physics research. Section A, Accelerators, spectrometers, detectors and associated equipment, 2016)
The amount of data produced by highly granular silicon tracking detectors in high energy physics experiments poses a major challenge to readout systems. At high collision rates, e.g. at LHC experiments, only a small fraction of data can be read out with currently used technologies. To cope with the requirements of future or upgraded experiments new data transfer techniques are required which offer high data rates at low power and low material budget. Wireless technologies operating in the 60GHz band or at higher frequencies offer high data rates and are thus a promising upcoming alternative to conventional data transmission via electrical cables or optical fibers. Using wireless technology, the amount of cables and connectors in detectors can be significantly reduced. Tracking detectors profit most from a reduced material budget as fewer secondary particle interactions (multiple Coulomb scattering, energy loss, etc.) improve the tracking performance in general. We present feasibility studies regarding the integration of the wireless technology at 60GHz into a silicon tracking detector. We use spare silicon strip modules of the ATLAS experiment as test samples which are measured to be opaque in the 60GHz range. The reduction of cross talk between links and the attenuation of reflections is studied. An estimate of the maximum achievable link density is given. It is shown that wireless links can be placed as close as 2cm next to each other for a layer distance of 10cm by exploiting one or several of the following measures: highly directive antennas, absorbers like graphite foam, linear polarization and frequency channeling. Combining these measures, a data rate area density of up to 11Tb/(s·m2) seems feasible. In addition, two types of silicon sensors are tested under mm-wave irradiation in order to determine the influence of 60GHz data transmission on the detector performance: an ATLAS silicon strip sensor module and an HV-MAPS prototype for the Mu3e experiment. No deterioration of the performance of both prototypes is observed.
Gesehen am 11.05.2020